A Phytase Characterized by Relatively High pH Tolerance and Thermostability from the Shiitake Mushroom Lentinus edodes. (21st March 2013) - Zhang, Guo-Qing; Wu, Ying-Ying; Ng, Tzi-Bun; Chen, Qing-Jun; Wang, He-Xiang
Abstract : A monomeric phytase with a molecular mass of 14 kDa was acquired from fresh fruiting bodies of the shiitake mushroom Lentinus edodes . The isolation procedure involved chromatography on DEAE-cellulose, CM-cellulose, Q-Sepharose, Affi-gel blue gel, and a final fast protein liquid chromatography-gel filtration on Superdex 75. The purified phytase demonstrated the unique N-terminal amino acid sequence DPKRTDQVN, which exhibited no sequence similarity with those of other phytases previously reported. It expressed its maximal activity at pH 5.0 and 37°C. Phytase activity manifested less than 20% change in activity over the pH range of 3.0–9.0, considerable thermostability with more than 60% residual activity at 70°C, and about 40% residual activity at 95°C. It displayed a wide substrate specificity on a variety of phosphorylated compounds with the following ranking: ATP > fructose-6-phosphate > AMP > glucose-6-phosphate > ADP > sodium phytate > β -glycerophosphate. The phytase activity was moderately stimulated by Ca 2+, but inhibited by Al 3+, Mn 2+, Zn 2+, and Cu 2+ at a tested concentration of 5 mM.